Gas-metal plasma source project for the separation technology - Yuferov, V.B.; Shariy, S.V.; Shvets, M.O.; Ozerov, A.N. (Вопросы атомной науки и техники, 2014)
This scientific paper deals with the project related to the gas-metal plasma source design. It describes the structure and electric power supply circuit. The consideration has been given to a possibility of the use of this source for the separation technology, in particular for the reprocessing of spent nuclear fuel (SNF). The requirements set to the source and parameters of the generated plasma have been devised. The efficiency of magnetoplasma reprocessing of SNF has been evaluated and the selection of metals and their oxides as the simulation media for the experiments carried out to reprocess spent nuclear fuel have been substantiated.